PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN DI PUSKESMAS - sundoro, totok; Syagita Alfa Thea (LPPM Akademi Manajemen Administrasi Yogyakarta, 2025)
Patient satisfaction is related to the quality of hospital services, by knowing the level of patient satisfaction, hospital management can improve the quality of services. Patient satisfaction can be created through good service by medical personnel in health institutions. The problems obtained from the interview results are poor service to patients because the service time is not fast enough so that there are still long queues, narrow waiting rooms and parking lots that are not spacious enough. Based on the results of interviews that have been conducted on patients at the Pleret Health Center, the results are that out of 8 patients, 2 patients said they were dissatisfied with the services at the Pleret Health Center. This study aims to determine the effect of service quality on patient satisfaction at the Pleret Health Center. This research method is quantitative with a cross-sectional approach. A sample of 99 Pleret Health Center patients using nonprobability sampling. Data were analyzed using Multiple Linear Regression. The results of the T test that there is an influence of the Reliability variable with a sig value= 0.574, Assurance with a sig value = 0.927, Tangible with a sig value = 0.373 on patient satisfaction. And the variables that do not affect Responsiveness with a sig value = 0.270 and the Empathy variable with a sig value = 0.034 on patient satisfaction. From the results of the F test, a significance level of 0.000 was obtained which is smaller than 0.05 (p <0.05). This it can be interpreted that reliability, responsiveness, assurance, empathy and tangible have a significant effect together on patient satisfaction at the Pleret Bantul Yogyakarta Health Center. From the results of the R test, it can be seen that the Adjusted R square test can produce a result of 0.421, which means that the level of relationship between the service quality variables (reliability, responsiveness, assurance, empathy, tangible) and the patient satisfaction variable is strong at 42.1% while the rest (100% - 42.1%) = 57.9% is influenced by other factors outside the variables studied.